Menumbuhkan Karakter Tanggungjawab AUD melalui Recalling Hadist Kebersihan di TK Muslimat NU Nurul Islam Kudus - Lina, Helina Himmatul Ulya (AGUSPATI Research Institute, 2021)
Characters of Early Childhood in Kindergarten that the researchers examined did not show a sense of responsibility for cleanliness. Precisely for the other characters who already look like religious characters and so on. Thus, the aim of the researcher is to determine the character formation of early childhood responsibility through Recalling the Hygiene Hadith in NU Muslimat Nurul Islam Kudus Kindergarten. The research that the researcher uses is a qualitative research type. This study uses a descriptive approach. Data collection techniques using observation, interviews and documentation. After the research data were collected, they were analyzed using descriptive data. The research question to be answered is how to grow the character of responsibility for early childhood through recalling the Hadith of Hygiene in NU Nurul Islam Muslim Kindergarten? Based on the results of the research that the author has done, it is concluded that through recalling the hadith, the cleanliness of the character of responsibility can grow in early childhood in the Muslimat NU Nurul Islam Kindergarten